O inquérito policial para o crime de homicídio: inquisitorialidade, discricionariedade e conflito em busca da verdade e de culpados - Juliana Neves Lopes Rodrigues (2011)
This dissertation examines the construction of the Police investigation in the crime of Homicide, based on a research of a specialized civil police station in Brazil. The objectives pursued consisted in understanding the practical role of the police officers in the construction of the investigation process, the way in which each player handles the formation of guilt, turning, in the process, witness into suspects, reflecting on the conflicting and disjointed action between police officers, clerks, crime scene investigators and others, expressed in the distrust of the work performed by each agent, demonstrating that coordination is only possible in the written materials of the inquérito policial. Another point is to discuss the discretionary police action as it selects what will be investigated and how investigation will proceed, and to explain how this selection is linked to organizational goals that ultimately prioritize productivity and efficiency, rather than the quality of the investigation. The analysis undertaken indicates that the construction of the inquérito policial is heavily influenced by the inquisitorial character of our criminal justice system revealing that the egalitarian principles of the law are systematically violated, because they are embedded in the hierarchical social order in which the police are responsible for all the burden of the Brazilian prosecution process, compromising the consolidation of the Democracy in our country (KANT DE LIMA, 1989).